IMPLEMENTATION OF THE COMMUNITY SERVICE PROGRAM IN IMPROVING STUDENTS' ENGLISH LITERACY AND NUMERACY SKILLS AT SDN 091409 SARIMATONDANG - Lastri Wahyuni Manurung; Galina Sitinjak; Anita Theresia Br Saragi; Hesty Malinda Manalu; Lusi Manurung; Rachel Br Sidabutar; Yuniarta Br Hutasoit (Universitas Galuh, 2023)
The Community Service Program (PKM) aims to improve students' English literacy and numeracy skills and develop a culture of English literacy and numeracy within SD Negeri 091409 Sarimatondang. This form of community service activity is carried out in 3 states of activity: Literacy and Numeracy Learning Activities in English